2014
DOI: 10.1530/eje-14-0388
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variation in plasma mitotane levels confirms the importance of trough level monitoring

Abstract: Objective: Mitotane is the drug of choice in patients with adrenocortical carcinoma. The anti-neoplastic effect is correlated with mitotane plasma levels, which render it crucial to reach and maintain the concentration above 14 mg/l. However, mitotane pharmacokinetics is poorly understood. The aim of this study was to investigate the variation in plasma mitotane levels during the day and the influence of a single morning dose. Design: A prospective case-control study was conducted to investigate the variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…16,34,41 Mitotane levels were not available for the entire patient population that spans 2 decades, and some of the levels that were reported were <14 mg/L. Notably, studies have cautioned that interpretation of this level can be misleading, as the serum level fluctuates greatly, depending on the timing of the blood draw, 42 and predicting the blood level based on the dosage is complex. 43 Additionally, many European studies have used the proposed European Network for the Study of Adrenal Tumors staging in analyses rather than the American Joint Committee on Cancer staging, as a SEER study has previously shown that European Network for the Study of Adrenal Tumors staging better discriminates between stage II and III patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,34,41 Mitotane levels were not available for the entire patient population that spans 2 decades, and some of the levels that were reported were <14 mg/L. Notably, studies have cautioned that interpretation of this level can be misleading, as the serum level fluctuates greatly, depending on the timing of the blood draw, 42 and predicting the blood level based on the dosage is complex. 43 Additionally, many European studies have used the proposed European Network for the Study of Adrenal Tumors staging in analyses rather than the American Joint Committee on Cancer staging, as a SEER study has previously shown that European Network for the Study of Adrenal Tumors staging better discriminates between stage II and III patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reasoning: As long as mitotane plasma levels are increasing and have not yet reached a plateau at >14 mg/L, mitotane plasma levels will be assessed every 3-4 weeks. Mitotane plasma level determination is best done as morning trough sampling, at least 12 h after the last dose, preventing false high levels (267). When mitotane plasma levels have reached a plateau, it is usually sufficient to measure blood levels every 6-12 weeks.…”
Section: R92 We Recommend Monitoring Of Blood Concentration Of Mitmentioning
confidence: 99%
“…For this reason, trough sampling is considered the standard management in monitoring mitotane levels and early morning appears the optimum time to assess trough levels. 45 …”
Section: Mitotane - Clinical Efficacy Dosage and Concentrationmentioning
confidence: 99%